Spatial perception and orientation in virtual environments – is virtual reality real enough? - Riecke, B. E. (39th annual meeting of the Society for Computers in Psychology (SCiP), 2009)
While Virtual Reality (VR) offers many experimental advantages including stimulus control and interaction in flexible, naturalistic multi-modal environments, there is mixed evidence whether humans perceive and behave similarly in computer-simulated environments. I will present and discuss several recent studies suggesting that care should be taken when using VR for perceptual/behavioral research: While naturalistic visual cues can, in principle, be sufficient to allow for real-world-like spatial orientation performance in VR, there is often a strong influence of both the content displayed (e.g., naturalism and cues available in VR) and the context (e.g., display type, size, and FOV).
Keywords: Riecke; Riecke_2009; bernhard-riecke; conferenceTalksWithoutPaper; iSpaceWeb; spatial updating; talkWithoutPaper